Safety and efficacy of traditional medicinal plant combinations for the treatment of sexually transmitted infections in Northern Maputaland, South Africa - Naidoo, Deshnee (My University, 2014)
Sexually transmitted infections (STIs) are a global concern and more specifically southern Africa has seen a tremendous upsurge in infection rates. KwaZulu-Natal is the province found to have the highest Human Immunodeficiency Virus and STI infection rates. From an ethnobotanical study conducted specifically in northern Maputaland (Mabibi, Tshongwe, Mseleni and Mbazwana), it was found that the lay people most often used plants in various combinations for the treatment of STI related symptoms. The use of these plant combinations were thus antimicrobially investigated and the toxicity properties determined. The dichloromethane: methanol (organic) and aqueous extracts were prepared for each plant in situ using collected ground dried plant material. The plants (individually and in combination) were investigated for toxic potential using the 3-[4,5-dimethyl-2-thiazol-yl]-2,5-diphenyl-2H-tetrazolium bromide (MTT) cellular viability assay on the human kidney epithelial (Graham) cell line. The antimicrobial activities for each sample, as well as for each combination, were then further investigated using the minimum inhibitory concentration (MIC) assay. The six STI pathogens investigated in this study were Candida albicans (ATCC 10321), Ureaplasma urealyticum (clinical strain), Oligella ureolytica (ATCC 43534), Gardnerella vaginalis (ATCC 14018), Trichomonas vaginalis (clinical strain) and Neisseria gonnorhoeae (ATCC 19424).
Thesis (M.Pharm.)--University of the Witwatersrand, Faculty of Health Sciences, 2013.
Keywords: Plants, Medicinal; Herbs, Medicinal; Sexually Transmitted Diseases--Drug Therapy